The use of design of experiment in modeling the bioethanol production from oil palm trunk sap - Nur Farhana, Jasney (2010)

(untitled)
Bioethanol, a biomass product, is one of the renewable energy sources that can be used as an automotive fuel. Therefore, bioethanol is essential in replacing the decreasing fossil fuels. The modeling of the experimental design for bioethanol production from oil palm trunk sap is conducted using Design Expert software version 7.1.6 (Stat Ease). This design of experiment is conducted to screen out the significant parameters that affecting the bioethanol production. The parameters that are being screened are the temperature, pH, inoculum percentage and agitation. The microbe involved is Saccharomylesn Cerevisiae Kyokai 7 since it accumulates bioethanol more than any other type of microbes. The Saccharomylesn Cerevisiae Kyokai 7 is cultured in the inoculums preparation and being fermented in the oil palm trunk sap for 48 hours. By using the 2-Level Full Factorial Design and Response Surface Methodology, the optimal parameters levels are determined. The best range value for temperature is in the range of 25oC, pH around 3, agitation speed in the range 250 rpm and inoculums percentage around 10 % for the maximum concentration of bioethanol